2015
DOI: 10.1179/2045772314y.0000000296
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Nintendo™ Wii Fit on gait, balance, and quality of life in individuals with incomplete spinal cord injury

Abstract: All subjects who participated in training with the NintendoTM Wii Fit demonstrated statistically significant improvements in gait speed and functional reach after seven weeks of training. Given the potential positive impact that the NintendoTM Wii Fit has on functional reach and gait speed in patients with iSCI, physical therapists may want to incorporate these activities as part of a rehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 32 publications
0
65
0
3
Order By: Relevance
“… Notes: SD, standard deviation. 1 Examples of excluded studies for this selection criteria are ( Morone et al, 2014 ; Wall et al, 2015 ). 2 Examples of excluded studies for this selection criteria are ( Bieryla & Dold, 2013 ; Janssen, Tange & Arends, 2013 ; Rendon et al, 2012 ; Bainbridge et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“… Notes: SD, standard deviation. 1 Examples of excluded studies for this selection criteria are ( Morone et al, 2014 ; Wall et al, 2015 ). 2 Examples of excluded studies for this selection criteria are ( Bieryla & Dold, 2013 ; Janssen, Tange & Arends, 2013 ; Rendon et al, 2012 ; Bainbridge et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Full body reaching tasks to virtual targets results in greater joint excursions as compared to real-world targets. Without the actual physical end-point, one can thus move beyond the visual target [8,14,19]. This explains the improvement in POMA-B in the EG in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Villiger et al [20] have found significant improvement in the BBS following a VR therapy in patients with incomplete SCI although the improvement was not sustainable. Considering the higher potential for ambulation in incomplete SCI, parameters such as gait speed, functionality, and quality of life have been assessed in a similar study by Wall et al [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, considerando os benefícios que a RV tem proporcionado aos indivíduos com LME, este estudo se justifica, pois se acredita que intervenções de reabilitação baseadas em RV tem sido um recurso altamente utilizado para melhorar a função, a deambulação e o equilíbrio de indivíduos com lesões neurológicas, conforme relatado por Wall et al (2015). Além disto, ela tem demonstrado ser uma importante ferramenta para estimular o engajamento e a motivação dos indivíduos durante o processo de reabilitação, podendo gerar um momento de prazer e diversão para eles.…”
Section: Introductionunclassified